Bilateral repetitive transcranial magnetic stimulation for treatment-resistant depression: a systematic review and meta-analysis of randomized controlled trials - Zhang,Y.Q. (2015)
There has been concern regarding the use of controversial paradigms for repetitive transcranial magnetic stimulation (rTMS) to manage treatment-resistant depression (TRD). This meta-analysis assessed the efficacy of bilateral rTMS compared with unilateral and sham rTMS in patients with TRD. PubMed, Embase, CENTRAL, PsycINFO, Web of Science, EAGLE and NTIS databases were searched to identify relevant studies, and randomized controlled trials (RCTs) on bilateral rTMS for TRD patients were included. The response was defined as the primary outcome, and remission was the secondary outcome. Ten RCTs that included 634 patients met the eligibility criteria. The risk ratio (RRs) of both the primary and secondary outcomes of bilateral rTMS showed non-significant increases compared to unilateral rTMS (RR=1.01, P=0.93; odds ratio [OR]=0.77, P=0.22). Notably, the RR of the primary bilateral rTMS outcome was significantly increased compared to that for sham rTMS (RR=3.43, P=0.0004). The results of our analysis demonstrated that bilateral rTMS was significantly more effective than sham rTMS but not unilateral rTMS in patients with TRD. Thus, bilateral rTMS may not be a useful paradigm for patients with TRD.